A high temperature resistant super hydrophobic aerogel material and preparation method thereof

By combining composite chopped fibers, composite nanofibers and modified silica sols with polyimide aerogels and grafting specific groups on the surface of the fibers and silica sols, the problems of poor hydrophobicity and low toughness of silica aerogel materials are solved, and aerogel materials that are resistant to high temperature, superhydrophobic, strong toughness and durability are achieved.

CN119241906BActive Publication Date: 2025-03-25SHANDONG RES & DESIGN ACADEMY OF IND CERAMICS
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411795744.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-03-25
Estimated Expiration
2044-12-09

AI Technical Summary

Technical Problem

Silica aerogel materials have problems such as poor hydrophobicity, low toughness, poor mechanical strength, poor durability and limited high temperature resistance, which limits their application in the field of aerospace materials.

Method used

Compound chopped fibers, composite nanofibers and modified silica sols are used to combine with polyimide aerogels. By grafting polymaleic anhydride, primary amine groups and secondary amine groups on the surface of the fibers, primary amine groups and secondary amine groups are grafted on the surface of the silicon sols, the crosslinking between the fibers and the aerogels is promoted, and the binding and dispersion of the material is improved.

Benefits of technology

The high temperature resistance, superhydrophobicity, toughness, mechanical strength, durability and thermal shock resistance of aerogel materials have been greatly improved, while reducing the thermal conductivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a high-temperature resistant super-hydrophobic aerogel material and a preparation method thereof, belonging to the technical field of aerogel materials. The preparation method comprises the following steps: preparing composite chopped fibers, preparing composite nanofibers, preparing modified silica sol, preparing composite aerogel powder, and compounding; the preparation of the composite chopped fibers comprises: introducing vinyl and introducing acid anhydride; the preparation of the composite nanofibers comprises mixing nanofibers, N-(2-aminoethyl)-3-aminopropyltriethoxysilane, anhydrous ethanol and water, stirring and refluxing at 45-55 DEG C for 5-6 hours, centrifuging, washing the precipitate with water and then drying; the preparation of the composite aerogel powder comprises mixing silica sol and modified silica sol, stirring at 10-25 DEG C, and centrifuging; the aerogel material prepared by the invention has excellent high-temperature resistance and super-hydrophobicity, isotropy, good toughness, high mechanical strength, low thermal conductivity, good durability and good thermal shock resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of aerogel materials, and in particular to a high temperature resistant super hydrophobic aerogel material and a preparation method thereof. Background Art

[0002] Aerogel material is a lightweight nano solid material with a nanoporous network structure, which is mainly divided into organic aerogel material, inorganic aerogel material and organic-inorganic hybrid aerogel material. Among them, organic aerogel material is based on organic matter, mainly including phenolic aerogel material, cellulose aerogel material, polyimide aerogel material, polyurethane aerogel material, chitosan aerogel material, etc.; inorganic aerogel material is based on inorganic matter, mainly including single aerogel material, oxide aerogel material, sulfide aerogel material, etc.; organic-inorganic hybrid aerogel material uses the advantages of organic and inorganic substances to realize the special functionalization of aerogel materials. Aerogel materials are widely used in thermal insulation, biomedicine, sound insulation, adsorption and other fields.

[0003] Silica aerogel material belongs to oxide aerogel material. It is a lightweight porous solid material with a pearl necklace-like skeleton network formed by interconnected nano-silica particles. Silica aerogel material is currently the most studied and mature aerogel material. The commonly used method for silica aerogel material is the sol-gel method, which is to obtain a sol through a precursor reaction of a silicon source, and then add a catalyst to hydrolyze and condense to obtain a wet gel, and then obtain a silica aerogel product through aging, drying and other steps. Silica aerogel has ultra-low bulk density, high porosity, large specific surface area and low thermal conductivity. It also has high elasticity and strong adsorption. It is widely used in electronic devices, energy storage batteries, aerospace materials and other fields.

[0004] However, silica aerogel materials have the following three disadvantages: First, poor hydrophobicity. The surface of silica aerogel materials contains a large amount of Si-OH, so it is hydrophilic, and it is easy to cause the skeleton structure to expand and rupture after absorbing water; second, it is relatively brittle, resulting in low toughness and poor mechanical strength of silica aerogel materials; third, poor durability. The bonding force between nano-silica particles is poor, resulting in the problem of powder loss in long-term use of silica aerogel materials; fourth, the high temperature resistance of silica aerogel materials is limited, and the long-term use temperature is 650-800°C. Since the temperature of the atmosphere reaches 1000°C, the aerospace materials used need to withstand a high temperature of 1000°C, which limits the application of silica aerogel materials in the field of aerospace materials.

[0005] In order to solve the above problems, the most commonly used method is to composite the silica aerogel material with a reinforcing phase. The reinforcing phase mainly includes inorganic fibers, organic fibers and polymer skeletons. Among them, inorganic fibers have excellent high temperature resistance and hydrophobicity and are the most commonly used reinforcing phase. However, when the silica aerogel material is compounded with the inorganic fiber, in order to obtain an isotropic aerogel material, the inorganic fiber to be used is chopped fiber or nanofiber. The aerogel material prepared from the chopped fiber or nanofiber has the following disadvantages: first, the chopped fiber or nanofiber is discontinuous in the aerogel material. When subjected to external force impact, the bonding force between the chopped fiber or nanofiber and the silica aerogel material is not strong, and the chopped fiber or nanofiber is extracted from the aerogel material before the chopped fiber or nanofiber is broken, resulting in poor toughening effect, and further resulting in poor toughness of the prepared aerogel material; second, due to the poor dispersibility of the chopped fiber or nanofiber in the aerogel material, the distribution of the chopped fiber or nanofiber is uneven, further resulting in poor toughness and mechanical strength of the prepared aerogel material, and also resulting in an increase in the thermal conductivity of the prepared aerogel material; third, the bonding force between the chopped fiber or nanofiber and the silica aerogel material is not strong, and the bonding force is greatly affected by temperature, resulting in poor thermal shock resistance of the prepared aerogel material. Summary of the invention

[0006] In view of the shortcomings of the prior art, the present invention provides a high-temperature resistant super-hydrophobic aerogel material and a preparation method thereof. The prepared aerogel material has excellent high-temperature resistance and super-hydrophobicity, isotropy, good toughness, high mechanical strength, low thermal conductivity, good durability and good thermal shock resistance.

[0007] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows:

[0008] A method for preparing a high temperature resistant super-hydrophobic aerogel material, comprising the following steps: preparing composite chopped fibers, preparing composite nanofibers, preparing modified silica sol, and preparing composite aerogel powder;

[0009] The preparation of the composite chopped fibers comprises the following steps: introducing vinyl and introducing acid anhydride;

[0010] The introduction of vinyl is performed by mixing chopped fibers, vinyl triethoxysilane and toluene, stirring and refluxing at 90-95° C. at a stirring speed of 50-100 rpm for 6-6.5 hours, filtering, washing the filter residue with toluene and drying to obtain chopped fibers after the introduction of vinyl;

[0011] The mass volume ratio of the chopped fibers, vinyl triethoxysilane, and toluene introduced into the vinyl is 140-150 g: 70-80 mL: 7500-8500 mL;

[0012] The chopped fibers are silicon carbide chopped fibers with a diameter of 10 μm and a length of 1 mm;

[0013] The acid anhydride is introduced, in a nitrogen atmosphere, the short-cut fibers after the introduction of vinyl, maleic anhydride and toluene are mixed, stirred at room temperature at a stirring speed of 50-100 rpm for 20-30 minutes, dibenzoyl peroxide is added, and the mixture is stirred and refluxed at a stirring speed of 50-100 rpm at 100-105° C. for 2.5-3 hours, filtered, and the filter residue is washed with toluene and then dried to obtain composite short-cut fibers;

[0014] The mass volume ratio of the chopped fibers introduced into the vinyl to the maleic anhydride, toluene, and dibenzoyl peroxide introduced into the acid anhydride is 140-150 g: 200-250 g: 7500-8500 mL: 1-1.1 g;

[0015] The composite nanofibers are prepared by mixing nanofibers, N-(2-aminoethyl)-3-aminopropyltriethoxysilane, anhydrous ethanol and water, stirring and refluxing at 45-55° C. at a stirring speed of 300-400 rpm for 5-6 hours, centrifuging, washing the precipitate with water and drying to obtain the composite nanofibers;

[0016] In the preparation of the composite nanofiber, the mass volume ratio of the nanofiber, N-(2-aminoethyl)-3-aminopropyltriethoxysilane, anhydrous ethanol, and water is 100-110 g: 80-90 mL: 5000-5200 mL: 260-280 mL;

[0017] The nanofibers are γ-alumina nanofibers with a diameter of 8 nm and a length of 300 nm;

[0018] The modified silica sol is prepared by mixing silica sol and N-(2-aminoethyl)-3-aminopropyltriethoxysilane, stirring and reflux at 45-55° C. and a stirring speed of 300-400 rpm for 5-6 hours to obtain the modified silica sol;

[0019] In the preparation of the modified silica sol, the volume ratio of silica sol to N-(2-aminoethyl)-3-aminopropyltriethoxysilane is 1000-1200:40-50;

[0020] The average particle size of silicon dioxide in the silica sol is 7 nm, the pH is 10, and the mass content of silicon dioxide is 30%;

[0021] The composite aerogel powder is prepared by mixing the silica sol and the modified silica sol, stirring at 10-25° C. at a stirring speed of 100-200 rpm for 30-40 minutes, and centrifuging to obtain the composite aerogel powder;

[0022] In the preparation of the composite aerogel powder, the volume ratio of silica sol to modified silica sol is 3000-3200:340-370;

[0023] The average particle size of silicon dioxide in the silica sol is 15 nm, the pH is 9.5, and the mass content of silicon dioxide is 30%;

[0024] The composite comprises mixing 4,4'-diaminodiphenyl ether and N-methyl pyrrolidone in a nitrogen atmosphere, stirring at a stirring speed of 100-300 rpm for 3-3.5 hours at 20-35°C, adding pyromellitic anhydride, continuing to stir for 2-2.5 hours, adding 1,3,5-tris(4-aminophenoxy)benzene, continuing to stir for 3.5-4 hours after the addition is completed, adding N-methyl pyrrolidone, acetic anhydride, pyridine, composite aerogel powder, composite chopped fibers, and composite The nanofibers are mixed and stirred at 55-60°C at a stirring speed of 100-300 rpm for 25-35 minutes; then added into a closed mold, and allowed to stand at room temperature in a nitrogen atmosphere until completely gelled; then allowed to stand at 50-55°C in a nitrogen atmosphere for 30-35 hours, and then completely immersed in N-methylpyrrolidone for impurity removal; then supercritical drying is performed using carbon dioxide; and then high-temperature treatment is performed in a nitrogen atmosphere to obtain a high-temperature resistant super-hydrophobic aerogel material;

[0025] In the composite, the mass volume ratio of 4,4'-diaminodiphenyl ether, N-methylpyrrolidone, pyromellitic anhydride, 1,3,5-tris(4-aminophenoxy)benzene, N-methylpyrrolidone, acetic anhydride, pyridine, composite aerogel powder, composite chopped fibers, and composite nanofibers is 170-180 g: 3700-4000 mL: 180-200 g: 10-11 g: 4600-5000 mL: 670-700 g: 540-560 g: 470-500 g: 70-75 g: 18-20 g;

[0026] The addition rate of the 1,3,5-tris(4-aminophenoxy)benzene is 0.4-0.5 g / min;

[0027] The impurity removal treatment is performed by standing at 30-35° C. for 40-46 hours, during which N-methylpyrrolidone is replaced every 10-12 hours;

[0028] The supercritical drying temperature is 50°C, the pressure is 12MPa, and the time is 14-15h;

[0029] The high temperature treatment is carried out by heating the temperature to 850-900°C at a heating rate of 2-3°C / min, and standing at 850-900°C for 1.5-2h.

[0030] A high temperature resistant super hydrophobic aerogel material prepared by the aforementioned preparation method.

[0031] Compared with the prior art, the present invention has the following beneficial effects:

[0032] (1) The preparation method of the high temperature resistant super hydrophobic aerogel material of the present invention comprises the following steps: a polyimide aerogel and a silica aerogel are composited, and composite short fibers, composite nanofibers, and modified silica sol are added, wherein the surface of the composite short fibers is grafted with polymaleic anhydride, the surface of the composite nanofibers is grafted with primary amine groups and secondary amine groups, and the surface of the modified silica sol is also grafted with primary amine groups and secondary amine groups. During the gelation process of the polyimide aerogel, the composite short fibers, the composite nanofibers, and the modified silica sol can be cross-linked in the polyimide aerogel, thereby solving the problem of poor bonding between the short fibers and the nanofibers and the aerogel material, and poor dispersibility in the aerogel. The problem of uniform distribution of chopped fibers and nanofibers can be solved, and the influence of temperature on the bonding force between chopped fibers, nanofibers and aerogel materials can be avoided, thereby improving the high temperature resistance, super hydrophobicity, toughness, mechanical strength, durability, thermal shock resistance of aerogel materials, and reducing thermal conductivity. In addition, the surface of modified silica sol also contains a certain amount of silanol, which can also be cross-linked in silica aerogel, thereby playing the role of cross-linking point, and can connect polyimide aerogel and silica aerogel, improve the uniformity of internal pore distribution and porosity, thereby further improving the high temperature resistance, toughness, mechanical strength, durability, thermal shock resistance of aerogel materials, and reducing thermal conductivity.

[0033] (2) The method for preparing the high temperature resistant super hydrophobic aerogel material of the present invention, wherein the prepared aerogel material can achieve isotropy;

[0034] (3) The method for preparing a high temperature resistant super hydrophobic aerogel material of the present invention, wherein the prepared aerogel material has super hydrophobicity, and the water contact angle of the prepared aerogel material is 150.7-153.2°;

[0035] (4) The method for preparing a high temperature resistant super hydrophobic aerogel material of the present invention has high mechanical strength and a compressive strength of 12.58-13.10 MPa;

[0036] (5) The method for preparing a high temperature resistant super hydrophobic aerogel material of the present invention has a low thermal conductivity of 0.029-0.032 W / (m·K);

[0037] (6) The method for preparing a high temperature resistant super hydrophobic aerogel material of the present invention has excellent high temperature resistance. The aerogel material prepared by the present invention is placed in air at 1000°C for 1 hour and naturally cooled to room temperature. The compressive strength of the aerogel material is 12.40-12.91 MPa and the thermal conductivity is 0.029-0.034 W / (m·K);

[0038] (7) The method for preparing a high temperature resistant super hydrophobic aerogel material of the present invention has good toughness. The aerogel material prepared by the present invention is compressed to 40% without breaking;

[0039] (8) The method for preparing the high temperature resistant super hydrophobic aerogel material of the present invention has good durability. The aerogel material prepared by the present invention is placed in air at 800°C for 30 days without powder falling off;

[0040] (9) The method for preparing a high temperature resistant super hydrophobic aerogel material of the present invention has good thermal shock resistance. The aerogel material prepared by the present invention is heated to 1000°C for 4 hours, kept at 1000°C for 10 minutes, and then cooled to 20°C by cold air as one cycle. A total of 20 cycles were performed without any cracks. DETAILED DESCRIPTION

[0041] In order to have a clearer understanding of the technical features, purposes and effects of the present invention, the specific implementation methods of the present invention are now described.

[0042] Example 1

[0043] A method for preparing a high temperature resistant super hydrophobic aerogel material, specifically comprising:

[0044] 1. Preparation of composite chopped fibers:

[0045] (1) Introduction of vinyl group: 140 g of chopped fibers, 70 mL of vinyl triethoxysilane, and 7500 mL of toluene were mixed, and the mixture was stirred and refluxed at 90° C. at a stirring speed of 50 rpm for 6 h, filtered, and the filter residue was washed with toluene and then dried to obtain chopped fibers after introduction of vinyl group;

[0046] The chopped fibers are silicon carbide chopped fibers with a diameter of 10 μm and a length of 1 mm;

[0047] (2) Introducing anhydride: In a nitrogen atmosphere, all the short-cut fibers after the introduction of vinyl obtained in the step of introducing vinyl in step (1), 200 g of maleic anhydride, and 7500 mL of toluene were mixed, and stirred at room temperature at a stirring speed of 50 rpm for 20 min, 1 g of dibenzoyl peroxide was added, and the mixture was stirred and refluxed at 100° C. at a stirring speed of 50 rpm for 2.5 h, filtered, and the filter residue was washed with toluene and then dried to obtain composite short-cut fibers;

[0048] 2. Preparation of composite nanofibers: 100 g of nanofibers, 80 mL of N-(2-aminoethyl)-3-aminopropyltriethoxysilane, 5000 mL of anhydrous ethanol, and 260 mL of water were mixed, stirred and refluxed at 45 ° C at a stirring speed of 300 rpm for 5 h, centrifuged, washed with water, and then dried to obtain composite nanofibers;

[0049] The nanofibers are γ-alumina nanofibers with a diameter of 8 nm and a length of 300 nm;

[0050] 3. Preparation of modified silica sol: 1000 mL of silica sol and 40 mL of N-(2-aminoethyl)-3-aminopropyltriethoxysilane were mixed, and the mixture was stirred and refluxed at 45° C. and 300 rpm for 5 h to obtain modified silica sol;

[0051] The average particle size of silicon dioxide in the silica sol is 7 nm, the pH is 10, and the mass content of silicon dioxide is 30%;

[0052] 4. Preparation of composite aerogel powder: 3000 mL of silica sol and 340 mL of modified silica sol were mixed, stirred at 10° C. and 100 rpm for 30 min, and centrifuged to obtain composite aerogel powder;

[0053] The average particle size of silicon dioxide in the silica sol is 15 nm, the pH is 9.5, and the mass content of silicon dioxide is 30%;

[0054] 5. Compounding: In a nitrogen atmosphere, mix 170g of 4,4'-diaminodiphenyl ether and 3700mL of N-methylpyrrolidone, stir at 100rpm for 3h at 20℃, add 180g of pyromellitic anhydride, continue stirring for 2h, slowly add 10g of 1,3,5-tris(4-aminophenoxy)benzene, control the addition rate to 0.4g / min, continue stirring for 3.5h after the addition is completed, add 4600mL N-methylpyrrolidone, 670g acetic anhydride, 540g pyridine, 470g composite aerogel powder, 70g composite chopped fibers, and 18g composite nanofibers were stirred at 55°C at a stirring speed of 100rpm for 25min; then added to a closed mold, and allowed to stand at room temperature in a nitrogen atmosphere until completely gelled; then allowed to stand at 50°C for 30h in a nitrogen atmosphere, and then completely immersed in N-methylpyrrolidone, and allowed to stand at 30°C for 40h, during which N-methylpyrrolidone was replaced every 10h; then supercritical drying was performed using carbon dioxide, and the supercritical drying temperature was controlled to be 50°C, the pressure to be 12MPa, and the time to be 14h; then in a nitrogen atmosphere, the temperature was increased to 850°C at a heating rate of 2°C / min, and allowed to stand at 850°C for 1.5h to obtain a high temperature resistant superhydrophobic aerogel material.

[0055] This embodiment also provides a high temperature resistant super hydrophobic aerogel material prepared by the aforementioned preparation method.

[0056] Example 2

[0057] A method for preparing a high temperature resistant super hydrophobic aerogel material, specifically comprising:

[0058] 1. Preparation of composite chopped fibers:

[0059] (1) Introduction of vinyl: 145 g of chopped fibers, 75 mL of vinyl triethoxysilane, and 8000 mL of toluene were mixed, stirred and refluxed at 92° C. at a stirring speed of 80 rpm for 6.5 h, filtered, and the filter residue was washed with toluene and dried to obtain chopped fibers after introduction of vinyl;

[0060] The chopped fibers are silicon carbide chopped fibers with a diameter of 10 μm and a length of 1 mm;

[0061] (2) Introducing anhydride: In a nitrogen atmosphere, all the short-cut fibers after the introduction of vinyl obtained in the step of introducing vinyl in step (1), 220 g of maleic anhydride, and 8000 mL of toluene were mixed, and stirred at room temperature at a stirring speed of 80 rpm for 25 min, 1 g of dibenzoyl peroxide was added, and the mixture was stirred and refluxed at 102° C. at a stirring speed of 80 rpm for 2.5 h, filtered, and the filter residue was washed with toluene and then dried to obtain composite short-cut fibers;

[0062] 2. Preparation of composite nanofibers: 105 g of nanofibers, 85 mL of N-(2-aminoethyl)-3-aminopropyltriethoxysilane, 5100 mL of anhydrous ethanol, and 270 mL of water were mixed, stirred and refluxed at 50 ° C at a stirring speed of 350 rpm for 5.5 h, centrifuged, washed with water, and then dried to obtain composite nanofibers;

[0063] The nanofibers are γ-alumina nanofibers with a diameter of 8 nm and a length of 300 nm;

[0064] 3. Preparation of modified silica sol: 1100 mL of silica sol and 45 mL of N-(2-aminoethyl)-3-aminopropyltriethoxysilane were mixed, and the mixture was stirred and refluxed at 50° C. and 350 rpm for 5.5 h to obtain modified silica sol;

[0065] The average particle size of silicon dioxide in the silica sol is 7 nm, the pH is 10, and the mass content of silicon dioxide is 30%;

[0066] 4. Preparation of composite aerogel powder: 3100 mL of silica sol and 350 mL of modified silica sol were mixed, stirred at 20°C and 150 rpm for 35 min, and centrifuged to obtain composite aerogel powder;

[0067] The average particle size of silicon dioxide in the silica sol is 15 nm, the pH is 9.5, and the mass content of silicon dioxide is 30%;

[0068] 5. Compounding: In a nitrogen atmosphere, mix 175g of 4,4'-diaminodiphenyl ether and 3800mL of N-methylpyrrolidone, stir at 200rpm for 3h at 30℃, add 190g of pyromellitic anhydride, continue stirring for 2h, slowly add 10.5g of 1,3,5-tris(4-aminophenoxy)benzene, control the addition rate to 0.4g / min, continue stirring for 3.5h after the addition is completed, add 4800mL N-methylpyrrolidone, 680g acetic anhydride, 550g pyridine, 480g composite aerogel powder, 72g composite chopped fibers, and 19g composite nanofibers were stirred at 57°C at a stirring speed of 200rpm for 30min; then added to a closed mold, and allowed to stand at room temperature in a nitrogen atmosphere until completely gelled; then allowed to stand at 52°C in a nitrogen atmosphere for 32h, and then completely immersed in N-methylpyrrolidone, and allowed to stand at 32°C for 44h, during which N-methylpyrrolidone was replaced every 11h; then supercritical drying was performed using carbon dioxide, and the supercritical drying temperature was controlled to be 50°C, the pressure to be 12MPa, and the time to be 14.5h; then in a nitrogen atmosphere, the temperature was raised to 880°C at a heating rate of 3°C / min, and allowed to stand at 880°C for 1.5h to obtain a high temperature resistant superhydrophobic aerogel material.

[0069] This embodiment also provides a high temperature resistant super hydrophobic aerogel material prepared by the aforementioned preparation method.

[0070] Example 3

[0071] A method for preparing a high temperature resistant super hydrophobic aerogel material, specifically comprising:

[0072] 1. Preparation of composite chopped fibers:

[0073] (1) Introduction of vinyl: 150 g of chopped fibers, 80 mL of vinyl triethoxysilane, and 8500 mL of toluene were mixed, stirred and refluxed at 95° C. at a stirring speed of 100 rpm for 6.5 h, filtered, and the filter residue was washed with toluene and dried to obtain chopped fibers after introduction of vinyl;

[0074] The chopped fibers are silicon carbide chopped fibers with a diameter of 10 μm and a length of 1 mm;

[0075] (2) Introducing anhydride: In a nitrogen atmosphere, all the short-cut fibers after the introduction of vinyl obtained in the step of introducing vinyl in step (1), 250 g of maleic anhydride, and 8500 mL of toluene were mixed, and stirred at room temperature at a stirring speed of 100 rpm for 30 min, 1.1 g of dibenzoyl peroxide was added, and the mixture was stirred and refluxed at 105° C. at a stirring speed of 100 rpm for 3 h, filtered, and the filter residue was washed with toluene and then dried to obtain composite short-cut fibers;

[0076] 2. Preparation of composite nanofibers: 110 g of nanofibers, 90 mL of N-(2-aminoethyl)-3-aminopropyltriethoxysilane, 5200 mL of anhydrous ethanol, and 280 mL of water were mixed, stirred and refluxed at 55 ° C at a stirring speed of 400 rpm for 6 h, centrifuged, washed with water, and then dried to obtain composite nanofibers;

[0077] The nanofibers are γ-alumina nanofibers with a diameter of 8 nm and a length of 300 nm;

[0078] 3. Preparation of modified silica sol: 1200 mL of silica sol and 50 mL of N-(2-aminoethyl)-3-aminopropyltriethoxysilane were mixed, and the mixture was stirred and refluxed at 55° C. and 400 rpm for 6 h to obtain modified silica sol;

[0079] The average particle size of silicon dioxide in the silica sol is 7 nm, the pH is 10, and the mass content of silicon dioxide is 30%;

[0080] 4. Preparation of composite aerogel powder: 3200 mL of silica sol and 370 mL of modified silica sol were mixed, stirred at 200 rpm for 40 min at 25°C, and centrifuged to obtain composite aerogel powder;

[0081] The average particle size of silicon dioxide in the silica sol is 15 nm, the pH is 9.5, and the mass content of silicon dioxide is 30%;

[0082] 5. Compounding: In a nitrogen atmosphere, mix 180g of 4,4'-diaminodiphenyl ether and 4000mL of N-methylpyrrolidone, stir at 300rpm for 3.5h at 35℃, add 200g of pyromellitic anhydride, continue stirring for 2.5h, slowly add 11g of 1,3,5-tris(4-aminophenoxy)benzene, control the addition rate to 0.5g / min, continue stirring for 4h after the addition is completed, add 5000mL N-methylpyrrolidone, 700g acetic anhydride, 560g pyridine, 500g composite aerogel powder, 75g composite chopped fibers, and 20g composite nanofibers were stirred at 60°C at a stirring speed of 300rpm for 35min; then added to a closed mold, and allowed to stand at room temperature in a nitrogen atmosphere until completely gelled; then allowed to stand at 55°C in a nitrogen atmosphere for 35h, and then completely immersed in N-methylpyrrolidone, and allowed to stand at 35°C for 46h, during which N-methylpyrrolidone was replaced every 12h; then supercritical drying was performed using carbon dioxide, and the supercritical drying temperature was controlled to be 50°C, the pressure to be 12MPa, and the time to be 15h; then in a nitrogen atmosphere, the temperature was increased to 900°C at a heating rate of 3°C / min, and allowed to stand at 900°C for 2h to obtain a high temperature resistant superhydrophobic aerogel material.

[0083] This embodiment also provides a high temperature resistant super hydrophobic aerogel material prepared by the aforementioned preparation method.

[0084] Comparative Example 1

[0085] On the basis of Example 1, the first step of preparing composite chopped fibers and the second step of preparing composite nanofibers are omitted, and in the sixth secondary composite step, silicon carbide chopped fibers with a diameter of 10 μm and a length of 1 mm are used instead of the composite chopped fibers, and γ-alumina nanofibers with a diameter of 8 nm and a length of 300 nm are used instead of the composite nanofibers.

[0086] The remaining operations are the same as those in Example 1.

[0087] Comparative Example 2

[0088] On the basis of Example 1, the step of preparing the modified silica sol in step 3 was omitted, and the addition of the modified silica sol in preparing the composite aerogel powder in step 4 was omitted.

[0089] The remaining operations are the same as those in Example 1.

[0090] Performance Test 1

[0091] The water contact angle, compressive strength and thermal conductivity of the aerogel materials prepared in Examples 1-3 and Comparative Examples 1-2 were tested. The test results are shown in Table 1:

[0092] Table 1

[0093]

[0094] Performance Test 2

[0095] The aerogel materials prepared in Examples 1-3 and Comparative Examples 1-2 were placed in air at 1000° C. for 1 hour, and naturally cooled to room temperature. The compressive strength and thermal conductivity of the aerogel materials were then tested. The test results are shown in Table 2:

[0096] Table 2

[0097]

[0098] Performance Test 3

[0099] The aerogel materials prepared in Examples 1-3 and Comparative Examples 1-2 were placed in air at 800°C for 30 days, and then naturally cooled to room temperature to observe whether there was a powder loss problem. The observation results are shown in Table 3:

[0100] Table 3

[0101]

[0102] Performance Test 4

[0103] The aerogel materials prepared in Examples 1-3 and Comparative Examples 1-2 were compressed to 40% and observed to see if they were broken. The results are shown in Table 4:

[0104] Table 4

[0105]

[0106] Performance Test 5

[0107] The aerogel materials prepared in Examples 1-3 and Comparative Examples 1-2 were heated to 1000°C for 4 hours, kept at 1000°C for 10 minutes, and then cooled to 20°C by cold air. This was regarded as one cycle. A total of 20 cycles were performed to observe whether the aerogel materials had cracks. The observation results are shown in Table 5:

[0108] Table 5

[0109]

[0110] It can be seen from the results of performance tests 1-5 that compared with the aerogel material prepared in Example 1, the aerogel material prepared in Comparative Example 1 has poor high temperature resistance, super hydrophobicity, toughness, mechanical strength, durability, and thermal shock resistance, and a higher thermal conductivity; the aerogel material prepared in Comparative Example 2 has poor high temperature resistance, super hydrophobicity, mechanical strength, durability, and thermal shock resistance, and a higher thermal conductivity.

[0111] Unless otherwise specified, all percentages used in the present invention are by mass.

[0112] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a high temperature resistant super hydrophobic aerogel material, characterized in that: The method comprises the following steps: preparing composite chopped fibers, preparing composite nanofibers, preparing modified silica sol, preparing composite aerogel powder, and compounding; The preparation of the composite chopped fibers comprises the following steps: introducing vinyl and introducing acid anhydride; The vinyl is introduced by mixing chopped fibers, vinyl triethoxysilane and toluene, stirring and refluxing at 90-95° C., filtering, washing the filter residue with toluene and drying to obtain chopped fibers after the vinyl is introduced; The chopped fibers introduced into the vinyl are silicon carbide chopped fibers with a diameter of 10 μm and a length of 1 mm; The introduction of acid anhydride comprises mixing the short fibers after the introduction of vinyl, maleic anhydride and toluene in a nitrogen atmosphere, stirring at room temperature, adding dibenzoyl peroxide, stirring and refluxing at 100-105° C., filtering, washing the filter residue and drying to obtain composite short fibers; The composite nanofibers are prepared by mixing nanofibers, N-(2-aminoethyl)-3-aminopropyltriethoxysilane, anhydrous ethanol and water, stirring and refluxing at 45-55° C. for 5-6 hours, centrifuging, washing the precipitate with water and drying to obtain the composite nanofibers; In the preparation of the composite nanofiber, the nanofiber is a γ-alumina nanofiber with a diameter of 8 nm and a length of 300 nm; The modified silica sol is prepared by mixing silica sol and N-(2-aminoethyl)-3-aminopropyltriethoxysilane, stirring and refluxing at 45-55° C. to obtain the modified silica sol; The composite aerogel powder is prepared by mixing the silica sol and the modified silica sol, stirring at 10-25° C., and centrifuging to obtain the composite aerogel powder; The composite comprises: mixing 4,4'-diaminodiphenyl ether and N-methylpyrrolidone in a nitrogen atmosphere, stirring at 20-35°C for 3-3.5h, adding pyromellitic anhydride, continuing stirring for 2-2.5h, adding 1,3,5-tri(4-aminophenoxy)benzene, continuing stirring for 3.5-4h after the addition, adding N-methylpyrrolidone, acetic anhydride, pyridine, composite aerogel powder, composite chopped fibers, and composite nanofibers, stirring at 55-60°C for 25-35min; then adding to a closed mold, standing at room temperature in a nitrogen atmosphere until complete gelation; then standing at 50-55°C in a nitrogen atmosphere for 30-35h, and then completely immersing in N-methylpyrrolidone for impurity removal; then using carbon dioxide for supercritical drying; and then performing high temperature treatment in a nitrogen atmosphere to obtain a high temperature resistant super hydrophobic aerogel material; In the composite, the high temperature treatment is performed by heating the temperature to 850-900° C. at a heating rate of 2-3° C. / min, and standing at 850-900° C. for 1.5-2 hours.

2. The method for preparing a high temperature resistant super hydrophobic aerogel material according to claim 1, characterized in that: The mass volume ratio of the chopped fibers, vinyl triethoxysilane and toluene introduced into the vinyl is 140-150 g: 70-80 mL: 7500-8500 mL.

3. The method for preparing a high temperature resistant super hydrophobic aerogel material according to claim 1, characterized in that: The mass volume ratio of the short-cut fibers introduced into the vinyl to the maleic anhydride, toluene and dibenzoyl peroxide introduced into the acid anhydride is 140-150g:200-250g:7500-8500mL:1-1.1g.

4. The method for preparing a high temperature resistant super hydrophobic aerogel material according to claim 1, characterized in that: In the preparation of the composite nanofiber, the mass volume ratio of the nanofiber, N-(2-aminoethyl)-3-aminopropyltriethoxysilane, anhydrous ethanol and water is 100-110 g: 80-90 mL: 5000-5200 mL: 260-280 mL.

5. The method for preparing a high temperature resistant super hydrophobic aerogel material according to claim 1, characterized in that: In the preparation of the modified silica sol, the volume ratio of silica sol to N-(2-aminoethyl)-3-aminopropyltriethoxysilane is 1000-1200:40-50; The average particle size of silicon dioxide in the silica sol is 7 nm, the pH is 10, and the mass content of silicon dioxide is 30%.

6. The method for preparing a high temperature resistant super hydrophobic aerogel material according to claim 1, characterized in that: In the preparation of the composite aerogel powder, the volume ratio of silica sol to modified silica sol is 3000-3200:340-370; The average particle size of silicon dioxide in the silica sol is 15 nm, the pH value is 9.5, and the mass content of silicon dioxide is 30%.

7. The method for preparing a high temperature resistant super hydrophobic aerogel material according to claim 1, characterized in that: In the composite, the mass volume ratio of 4,4'-diaminodiphenyl ether, N-methylpyrrolidone, pyromellitic anhydride, 1,3,5-tris(4-aminophenoxy)benzene, N-methylpyrrolidone, acetic anhydride, pyridine, composite aerogel powder, composite chopped fibers, and composite nanofibers is 170-180 g: 3700-4000 mL: 180-200 g: 10-11 g: 4600-5000 mL: 670-700 g: 540-560 g: 470-500 g: 70-75 g: 18-20 g; The addition rate of the 1,3,5-tris(4-aminophenoxy)benzene is 0.4-0.5 g / min; The impurity removal treatment is performed by standing at 30-35° C. for 40-46 hours, during which N-methylpyrrolidone is replaced every 10-12 hours; The supercritical drying temperature is 50° C., the pressure is 12 MPa, and the time is 14-15 hours.

8. A high temperature resistant super hydrophobic aerogel material prepared by the preparation method according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Preparation method of crosslinked polyimide silicon dioxide mixed gas gel

    CN104341594A

  • Electrogel composite material with low heat transfer and low dielectric properties and preparation method thereof

    CN117004077A